Menuju Pemilu Adil: Sosialisasi Pengawasan Pemilu bagi Calon Mahasiswa Baru UIB - Juwita Sulputri; Vivi Chandrawati; Muhammad Hauzan Suhenal; Kellen Kellen; Jupiter Agustio Liu Siaw Ping; Noval Christanto; Wilson Wilson; M. Rashif Zabadi R; Mega Augustina Ng; Marcellina Marcellina; Kendrick Hartson (National Conference for Community Service Project (NaCosPro), 2023)
General Elections mean implementing people's sovereignty, carried out directly, publicly, freely, confidentially, honestly, and fairly within the Unitary State of Indonesia. They are based on Pancasila and the 1945 Constitution of the Republic of Indonesia. The collaboration between Bawaslu and Universitas International Batam students aims to provide socialization for the general election. This socialization is intended to give an understanding to prospective new students at Batam International University who will become beginner voters in the 2024 election. Beginner election voters are individuals aged 17 years and over or under 17 years and over who have been married, according to RI Constitution No. 7 of 2017, Article 348. By organizing this socialization activity, Batam International University students can fully comprehend the material provided and understand their rights as voters for the 2024 simultaneous election. They are also encouraged to participate in election supervision as first-time voters.